Curriculum Innovation in Islamic Religious Education: Responding to Globalization and the Demands of 21st-Century Skills - IMAM KHOWIM (JURNAL ILMIAH INNOVATIVE (Jurnal Pemikiran Dan Penelitian), 2026)
This study analyzes curriculum innovation in Islamic Religious Education in response to globalization and the demands of 21st-century skills. Using a qualitative research design, data were obtained from curriculum documents, teacher interviews, and classroom observations. The findings reveal that innovative IRE curricula emphasize critical thinking, communication, collaboration, and creativity while integrating Islamic values. However, implementation challenges include limited teacher preparedness and rigid assessment systems. The study highlights the need for flexible curriculum models that balance religious authenticity with global competencies. This research contributes to curriculum studies by proposing a contextualized framework for innovative Islamic education in the global era.